Protein synthesis and targeting in yeast - Brown, Alistair J.; North Atlantic Treaty Organization. Scientific Affairs Division; NATO Advanced Research Workshop on Protein Synthesis and Targeting in Yeast (1992 : Canterbury, England) (Berlin : Springer, 1993)
42